Dental Pain in Maryland School Children - Clemencia M. Vargas, DDS, PhD; Mark D. Macek, DDS, DrPH; Harold S. Goodman, DMD, MPH, Mark L. Wagner (Blackwell Synergy, 2005)
To describe the lifetime prevalence of dental pain among Maryland’s school age children.